Environmental factors restrict the invasion process of Limnoperna fortunei (Mytilidae) in the Neotropical region: A case study from the Andean tributaries - Darrigran, Gustavo Alberto (2011)
The golden mussel Limnoperna fortunei was introduced into Argentina in 1991 and has since been spreading through the Plata and Guaíba basins at a rate of 240 km.year−1. To assess their ability to invade the Andean tributaries of the Plata Basin (Pilcomayo, Bermejo and Salado del Norte rivers), their current range was assessed and related to the abiotic parameters of sites where they were present and absent. These data were then compared with their known tolerances to identify possible barriers to invasion. Outputs suggested that three environmental parameters are barriers to invasion: salinity and river flow intermittence in different sectors of the rivers Pilcomayo and Salado del Norte, and concentration of suspended sediments in the Bermejo River and in the upper reaches of the Salado del Norte and Pilcomayo rivers. The importance of these findings is discussed in relation to using environmental data to infer the invasion possibilities and the utility of environmental data to better understand invasion patterns and processes.